The wisdom of teams : creating the high-performance organization - Katzenbach, Jon R., 1932- (Recorded Books, 2017)
The Wisdom of Teams is the definitive work on how to create high-performance teams in any organization. Having sold nearly a half million copies and been translated into more than fifteen languages, the authors' clarion call that teams should be the basic unit of organization for most businesses has permanently shaped the way companies reach the highest levels of performance. Wisdom lies in recognizing a team's unique potential to deliver results and in understanding its many benefits-development of individual members, team accomplishments, and stronger companywide performance. Katzenbach and Smith's comprehensive classic is the essential guide to unlocking the potential of teams in your organization.